Writing at Primary Grades: Memories, Stories and Praxis - Souza Balsan, Silvana Ferreira de [UNESP]; Souza, Renata Junqueira de [UNESP] (Univ Federal Espirito Santo, 2015)
This paper tries to discuss the historical processes of teaching and learning of writing in school. Then, from a didactic sequence performed with students from the 4th grade of elementary school we will present a proposal based on the interactionist conception (VYGOTSKY, 1998, 2008, 2014), consisting of reading practices (LEFFA, 1996a, 1996b; SOLE, 1998) and writing (FIAD; MAYRINK-SABINSON, 2004; COSTA VAL [.. et al], 2009; RUIZ, 2013), which values the dialogue and interaction between the children and the teacher. The practices presented and discussed in this article were developed and implemented in a City Department of Education at Sao Paulo State. We propose an intervention and analyze some written records of the students in a learning situation. We conclude that, inside the school, we have to provide meaningful activities of reading and writing and that these should be generated from a praxis guided dialogue.
Keywords: Education; Teaching and Learning; Training of Teachers and Writers; Dialogic Education